Evaluasi Implementasi Sistem Pengendalian Persediaan dengan Metode EOQ - Myra Andriana (Jurnal Bisnis Kreatif dan Inovatif, 2024)
The inventory system that has been used has faced various problems, namely that there are often errors in the process of implication in Ms.Excel because the data is large enough and must clean old data. The absence of history of who has entered and accessed into Ms.Excel makes the security of the data in it reduced. To solve the problems faced, an inventory information system was developed using the WEB-based EOQ method. This study aims to analyze the suitability of the developed system with the needs of the user. The results showed that the inventory information system has been integrated with the system so that it is more effective and efficient.. This is evidenced by system testing, internal and external validation carried out by expert experts, plus effectiveness tests between the old system and the new system.